2012
DOI: 10.1093/infdis/jir842
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Vaccination With Recombinant Adenovirus Reduces Splenic Parasite Burden in Experimental Visceral Leishmaniasis

Abstract: Therapeutic vaccines, when used alone or in combination therapy with antileishmanial drugs, may have an important place in the control of a variety of forms of human leishmaniasis. Here, we describe the development of an adenovirus-based vaccine (Ad5-KH) comprising a synthetic haspb gene linked to a kmp11 gene via a viral 2A sequence. In nonvaccinated Leishmania donovani–infected BALB/c mice, HASPB- and KMP11-specific CD8+ T cell responses were undetectable, although IgG1 and IgG2a antibodies were evident. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 48 publications
4
69
1
1
Order By: Relevance
“…22 In addition, preclinical studies in a murine VL model have demonstrated the therapeutic efficacy of a single-dose adenoviral vaccine expressing kinetoplastid membrane protein-11 and hydrophilic acylated surface protein B1. 23 Following this work, a chimp adenovirus-vectored vaccine, ChAd63-KH (United Kingdom), was developed and has exhibited a good safety [24][25][26] Lastly, vaccine development via genetically modified, liveattenuated whole parasites were also summarized in the workshop. 27 These vaccines are intended to mimic the natural course of infection to facilitate a strong, long-lasting, and protective immune response.…”
Section: Vl Vaccine Research and Developmentmentioning
confidence: 99%
“…22 In addition, preclinical studies in a murine VL model have demonstrated the therapeutic efficacy of a single-dose adenoviral vaccine expressing kinetoplastid membrane protein-11 and hydrophilic acylated surface protein B1. 23 Following this work, a chimp adenovirus-vectored vaccine, ChAd63-KH (United Kingdom), was developed and has exhibited a good safety [24][25][26] Lastly, vaccine development via genetically modified, liveattenuated whole parasites were also summarized in the workshop. 27 These vaccines are intended to mimic the natural course of infection to facilitate a strong, long-lasting, and protective immune response.…”
Section: Vl Vaccine Research and Developmentmentioning
confidence: 99%
“…Cependant, malgré les grandes avancées dans la compréhension de la biologie du parasite et de la réponse de l'hôte, il existe encore les virus recombinants et les vaccins ADN. Un vaccin à base d'adénovirus recombinant codant pour deux antigènes de leishmanies, KMP-11 et HASPB, est en cours de développement par une équipe anglaise [55]. Un autre projet, mis en place dans le 7 e programme cadre européen, auquel contribue l'équipe de l'IP Tunis, consiste à développer un vaccin à base d'ADN codant pour cinq antigènes de Leishmania…”
Section: La Vaccination Est-elle Faisable ? Quels Sont Les Pré-requisunclassified
“…Among some of these properties, it is worth mentioning that: i-cruzipain is expressed in all developmental stages and strains of the parasite 10 ; ii-it is accumulated in the lysosomes, it is secreted and also present at surface level, being able to hydrolyze immunoglobulins 11 ; iii-it plays an important role in the process of internalization within mammalian cells 12 ; and iv-it is highly immunogenic in natural infection. 13 Recent improvements to DNA vaccines and the potential and flexibility of DNA as a potent immunization strategy for inducing both humoral and cell-mediated immune responses, make them an ideal therapeutic approach for treating or eliminating chronic disease, as it was shown in multiple sclerosis, 14 human papillomavirus, 15,16 hepatitis B 17 , human immunodeficiency virus, 18,19 simian immunodeficiency virus, 20 Mycobacterium tuberculosis, 21 Leishmania spp., 22,23 Schistosoma mansoni, 24 as well as against T. cruzi. 25,26 We have previously reported the efficacy of attenuated Salmonella enterica (S) carrying plasmid encoding cruzipain (SCz) to protect against T. cruzi infection.…”
Section: Introductionmentioning
confidence: 99%